Six-Rowed Spike3 (VRS3) Is a Histone Demethylase That Controls Lateral Spikelet Development in Barley - van Esse, G. Wilma (Plant Physiol, 2017)
The complex nature of crop genomes has long prohibited the efficient isolation of agronomically relevant genes. However, recent advances in next-generation sequencing technologies provide new ways to accelerate fine-mapping and gene isolation in crops. We used RNA sequencing of allelic six-rowed spike3 (vrs3) mutants with altered spikelet development for gene identification and functional analysis in barley (Hordeum vulgare). Variant calling in two allelic vrs3 mutants revealed that VRS3 encodes a putative histone Lys demethylase with a conserved zinc finger and Jumonji C and N domain. Sanger sequencing of this candidate gene in independent allelic vrs3 mutants revealed a series of mutations in conserved domains, thus confirming our candidate as the VRS3 gene and suggesting that the row type in barley is determined epigenetically. Global transcriptional profiling in developing shoot apical meristems of vrs3 suggested that VRS3 acts as a transcriptional activator of the row-type genes VRS1 (Hv.HOMEOBOX1) and INTERMEDIUM-C (INT-C; Hv.TEOSINTE BRANCHED1). Comparative transcriptome analysis of the row-type mutants vrs3, vrs4 (Hv.RAMOSA2), and int-c confirmed that all three genes act as transcriptional activators of VRS1 and quantitative variation in the expression levels of VRS1 in these mutants correlated with differences in the number of developed lateral spikelets. The identification of genes and pathways affecting seed number in small grain cereals will enable to further unravel the transcriptional networks controlling this important yield component.